Calpain inhibitor and ibudilast rescue β cell functions in a cellular model of Wolfram syndrome - Nguyen, Lien D.; Fischer, Tom Tobias; Abreu, Damien; Arroyo, Alfredo; Urano, Fumihiko; Ehrlich, Barbara E. (Proceedings of the National Academy of Sciences of the United States of America, 2020)
Wolfram syndrome is a rare multisystem disease characterized by childhood-onset diabetes mellitus and progressive neurodegeneration. Most cases are attributed to pathogenic variants in a single gene, Wolfram syndrome 1 (WFS1). There currently is no disease-modifying treatment for Wolfram syndrome, as the molecular consequences of the loss of WFS1 remain elusive. Because diabetes mellitus is the first diagnosed symptom of Wolfram syndrome, we aimed to further examine the functions of WFS1 in pancreatic β cells in the context of hyperglycemia. Knockout (KO) of WFS1 in rat insulinoma (INS1) cells impaired calcium homeostasis and protein kinase B/Akt signaling and, subsequently, decreased cell viability and glucose-stimulated insulin secretion. Targeting calcium homeostasis with reexpression of WFS1, overexpression of WFS1’s interacting partner neuronal calcium sensor-1 (NCS1), or treatment with calpain inhibitor and ibudilast reversed deficits observed in WFS1-KO cells. Collectively, our findings provide insight into the disease mechanism of Wolfram syndrome and highlight new targets and drug candidates to facilitate the development of a treatment for this disorder and similar diseases.